Comparison between two forms of granular activated carbon for the removal of pharmaceuticals from different waters - Lima, Lisandra [UNESP]; Baêta, Bruno E.L.; Lima, Diego R.S.; Afonso, Robson J.C.F.; De Aquino, Sérgio F.; Libânio, Marcelo (Taylor & Francis, 2016)
The aim of this study was to evaluate the performance of two forms of basic granular activated carbon (GAC), mineral (pH = 10.5) and vegetal (pH = 9), for the removal of three pharmaceuticals, as sulphamethoxazole (SMX), diclofenac (DCF) and 17β-estradiol (E2), from two different matrices: fortified distilled (2.4-3.0mgL-1 and pH from 5.5 to 6.5) and natural (∼1.0mgL-1 and pH from 7.1 to 7.2) water in a bench scale. The Rapid Small-Scale Column Test used to assess the ability of mineral and vegetal GAC on removal of such pharmaceuticals led to removal capacities varying from 14.9 to 23.5mgg-1 for E2, from 23.7 to 24.2mgg-1 for DCF and from 20.5 to 20.6mgg-1 for SMX. Removal efficiencies of 71%, 88% and 74% for DCF, SMX and E2, respectively, were obtained at breakthrough point when using mineral GAC, whereas for the vegetal GAC the figures were 76%, 77% and 65%, respectively. The carbon usage rate at the breakthrough point varied from 11.9 to 14.5Lg-1 for mineral GAC and from 8.8 to 14.8Lg-1 for vegetal GAC. Mineral CAG also exhibited the best performance when treating fortified natural water, since nearly complete removal was observed for all contaminants in the column operated for 22h at a carbon usage rate of 2.9Lg-1.
Keywords: adsorption; endocrinedisrupting compounds; granular activated carbon; Pharmaceuticals; water treatment